2018
DOI: 10.1186/s12955-018-0942-7
|View full text |Cite
|
Sign up to set email alerts
|

The capability set for work – correlates of sustainable employability in workers with multiple sclerosis

Abstract: BackgroundThe aim of this study was to examine whether work capabilities differ between workers with Multiple Sclerosis (MS) and workers from the general population. The second aim was to investigate whether the capability set was related to work and health outcomes.MethodsA total of 163 workers with MS from the MS@Work study and 163 workers from the general population were matched for gender, age, educational level and working hours. All participants completed online questionnaires on demographics, health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 32 publications
(41 reference statements)
3
26
0
Order By: Relevance
“…Also included in these 20 are studies in which it was not clear whether fatigue was analyzed as a dichotomous or continuous variable. Most studies reported cross-sectional data ( n = 17) [ 66 81 ]. Most studies were conducted in Europe and North America ( n = 16) [ 66 68 , 71 79 , 81 84 ], one was conducted in Argentina [ 69 ], one in Australia [ 85 ], and two did not clearly report the study location [ 70 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also included in these 20 are studies in which it was not clear whether fatigue was analyzed as a dichotomous or continuous variable. Most studies reported cross-sectional data ( n = 17) [ 66 81 ]. Most studies were conducted in Europe and North America ( n = 16) [ 66 68 , 71 79 , 81 84 ], one was conducted in Argentina [ 69 ], one in Australia [ 85 ], and two did not clearly report the study location [ 70 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies reported cross-sectional data ( n = 17) [ 66 81 ]. Most studies were conducted in Europe and North America ( n = 16) [ 66 68 , 71 79 , 81 84 ], one was conducted in Argentina [ 69 ], one in Australia [ 85 ], and two did not clearly report the study location [ 70 , 80 ]. FSS and MFIS were the most commonly used tools to measure fatigue, used in seven studies each.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is possible that sustainable employment for employees with various disabilities, such as those associated with multiple sclerosis [95], could be facilitated by telework. The converse of this relationship is that caregivers of family members often maintain employment by engaging in flexible work arrangements [96] and generally value flexible work arrangements [64].…”
Section: Sdg 8: Decent Work and Economic Growthmentioning
confidence: 99%
“…Furthermore, it is possible that sustainable employment for employees with various disabilities, such as those associated with multiple sclerosis [96], could be facilitated by telework. The flip side of this relationship is that caregivers of family members often maintain employment by engaging in flexible work arrangements [97], and generally value flexible work arrangements [63].…”
Section: Sdg 8: Decent Work and Economicmentioning
confidence: 99%